1.90-1.88Ga arc magmatism of central Fennoscandia: geochemistry, U-Pb geochronology, Sm-Nd and Lu-Hf isotope systematics of plutonic-volcanic rocks from southern Finland - J. KARA; M. VÄISÄNEN; Å. JOHANSSON; Y. LAHAYE; H. O'BRIEN; O. EKLUND (Geologica Acta, 2016)
The earliest Svecofennian magmatism in southern Finland has been dated at 1.90-1.88Ga. As an example of this, the Orijärvi (ca. 1.89Ga) and Enklinge (ca. 1.88Ga) volcanic centres comprise bimodal plutonic batholiths surrounded by volcanic rocks of comparable ages and chemical compositions. Here, we report geochemical and Sm-Nd isotope data from intrusive and extrusive samples, combined with zircon U-Pb and Lu-Hf isotopes for granodiorites from both study areas. The samples range from gabbros to granites and indicate a subduction-related continental margin setting. The zircons from the Orijärvi granodiorite define an age of 1892±4Ma whereas the Enklinge granodiorite yields an age of 1882±6Ma. Several inherited ages of 2.25-1.95Ga as well as younger ages of 1.86-1.80Ga were found in the Enklinge granodiorite. The initial εNd values from the mafic rocks from both locations fall in the range +1.1 to +2.9 whereas the felsic rocks exhibit initial εNd values of -0.4 to +1.2. The magmatic zircons from the Orijärvi and Enklinge granodiorites show average initial εHf values of -1.1 (at 1892Ma) and zero (at 1882Ma), respectively, each with a spread of about 7 ε-units. The initial εHf values for the inherited zircons from Enklinge range from +3.5 to +7.6 with increasing age. The Sm-Nd data indicate that the mafic rocks were derived from a “mildly depleted” mantle source while the felsic rocks show larger crustal contribution. Also, the variation in εHf values indicates minor mixing between mildly depleted mantle derived magmas and crustal sources. U-Pb ages and Hf isotopes for inherited zircons in the Enklinge granodiorite suggest the presence of juvenile Svecofennian “proto-crust” at depth.